The Effect Of Using Loose Parts Learning Materials On The Mathematical Skills Of Year 2 Pupils At SD Negeri 09 Sayan - Ratu Nurhaliza; Ahmad Khoiri; M. Akip (CV PUTRA PUBLISHER, 2026)
The purpose of this study was to determine whether the application of loose part learning media can improve students' numeracy skills in mathematics learning. This study employed a quantitative method using a One-Group Pre-Posttest design with a sample comprising 16 Year 2 students. Data were collected through validity tests (trial questions) and reliability (α = 0.7), then analysed using the Wilcoxon test with SPSS 21. The results showed a significant increase (Sig. 0.001 < 0.05), with the post-test mean (66.56) higher than the pre-test mean (52.19). This finding demonstrates that loose parts are effective in improving students’ numeracy skills. Consequently, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. It can therefore be concluded that there is a difference in the average learning outcomes between the pre-test and post-test, indicating a significant change following the intervention. This confirms that there is an effect of using loose parts as a learning medium on the numeracy skills of Year 2 pupils at SDN 09 Sayan.